Jejunal Polyps that Lead to Small Bowel Intussusception in Adults: A Rare Case Report - Nazir, Shahid; Munir, Ambreen; Sulman, Sehrish; ., Qazi Waleed-u-Zaman; Yar Muhammad, Aisha (Journal of Liaquat University of Medical & Health Sciences, 2020)
Small intestine polyps are very rare in adults. Incidental finding of those polyps; sending them for histopathology that comes out to be Peutz-Jeghers syndrome (PJS) is extremely rare. PJS is an inherited disease characterized with typical hamartomas polyps in intestine along with distinctive skin pattern and mucocutaneous pigmentation. Gene mutation is responsible for 93% of PJS cases, among which majority of cases occur due to mutation in STK11 gene. PJS patients have 15-fold higher risk of developing cancer, including intestinal, extra-intestinal, breast, lung, pancreatic and colorectal cancer. Although PJS incidence is very low but its early recognition is very important for lowering morbidity and mortality. In this study, we have reported a very rare case of PJS in adults that was operated for small bowel obstruction secondary to intussusception. These cases are very rare in literature.